Perubahan Bacaan Syair dalam Kitab Maulid Āḍyā ʾulāmiʿ Di Masyarakat Kabupaten Tanjung Jabung Barat (Kajian Fonetik) - Reko, Muhammad Reko; Zaini, Hisyam; Afifah, Nur; Suja'i, Mahmud; Muhammad Reko, Reko (Institut Agama Islam Negeri Metro, 2025)
This study aims to describe the mispronunciations of Hijaiyah letters in the recitation of the Maulid Āḍyā ʾUlāmiʿ verses among the community in Tanjung Jabung Barat Regency. The researcher employs articulatory phonetics theory to examine how the sounds in the verses are produced and to observe the phonetic shifts in Arabic pronunciation due to the influence of the local language in Tanjung Jabung Barat. This study will discuss the forms of pronunciation changes and the factors that influence them in the recitation of the Maulid Āḍyā ʾUlāmiʿ. In addition, the researcher uses a descriptive qualitative method. Data collection techniques include regular observation, in-depth interviews, and documentation. The results of the study reveal mispronunciations of the letters ʿAyn (ع), Ghain (غ), Ḥāʾ (ح), Thāʾ (ث), Qāf (ق), and Ṣād (ص). These changes include the letter ʿAin being replaced with hamzah, Ghain changing to g, Ḥāʾ becoming hāʾ, Ṯāʾ becoming sīn, Qāf changing to kāf or hamzah, and Ṣād becoming sīn. These pronunciation errors are caused by the influence of the Jambi Malay dialect applied when reading the Arabic-language verses of Āḍyā ʾUlāmi.